Antara citra dan realita: Peran CSR terhadap return saham dalam bayang-bayang penghindaran pajak - Nurhayati, Putri Fitria Indah; Adam, Helmy (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study aims to test and analyze the effect of corporate social responsibility on stock returns, as well as the role of tax avoidance as a moderating variable in health service and pharmaceutical sector companies listed on the IDX for the 2021-2023 period. Methods – This study uses a quantitative approach with secondary data sources. Data analysis was conducted using Moderated Regression Analysis (MRA) to test the interaction relationship between CSR and tax avoidance on stock returns. Findings - The results of this study indicate that CSR disclosure has a positive effect on stock returns. Meanwhile, tax avoidance does not moderate the effect of CSR disclosure on stock returns. Implications - This study provides theoretical contributions to the development of signaling and legitimacy theory, as well as practical benefits for academics, companies, investors, and government in understanding the relationship between CSR, tax avoidance, and stock returns as a basis for decision making and policy making. Originality - This study enriches the literature by presenting tax avoidance as a moderating variable in the relationship between CSR and stock returns, which has rarely been examined in previous studies.